Μελέτη της επίδρασης του όζοντος στη μικροχλωρίδα σφάγιων πουλερικών - Πίπη, Άννα (Τμήμα Γεωπονικών Επιστημών,Βιοτεχνολογίας και Τεχνολογίας Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, 2012)
Ozone is a highly active substance which causes oxidative damages to microorganisms, consequently inducing apoptosis without releasing hazardous residues. This study investigates the effect of ozone on the microbial quality of poultry carcasses after the immersion into ozonated water. Carcasses were immersed into ozonated water, after evisceration and rinsing and samples were taken before and after immersion using two different methods: i) whole carcass swabs (n=20, 10 before and 10 after) and ii) pooled neck-skin samples (n=80, 40 before and 40 after). All samples were analyzed for Total Viable Count (TVC), Coliforms, E. coli, S. aureus and Yeasts and Moulds. A significant reduction of 0,5 log was only observed for the TVC, whilst all the other parameters didn’t present significant reductions. This can be attributed to the concentration of ozonated water which was initially 15 ppm but after immersion of the carcasses was significantly reduced due to its reaction with organic material, specifically blood and fat, which were dissolved in the ozonated water. Ozone application is particularly promising in reducing pathogenic and spoilage microorganisms in poultry but it has to be done in a matter, which will ensure that the concentration of ozone is continuously maintained at drastic levels.
Keywords: Ozone; Poultry; Όζον; Πουλερικά